2008
DOI: 10.1021/om800577x
|View full text |Cite
|
Sign up to set email alerts
|

NHC Complexes of Osmium Clusters: A Structural and Reactivity Study

Abstract: A carbene transfer agent, 1,3-bis-(2,4,6-trimethylphenyl)imidazol-2-ylidene-silver(I)chloride ([IMes]-AgCl), was treated with various osmium clusters. Reaction of ([IMes]AgCl) with [Os 3 (µ-H) 2 (CO) 10 ] gave [Os 3 (µ-H)(µ-Cl)(CO) 9 (IMes)] (1), an osmium N-heterocyclic carbene complex. The reaction of ([IMes]AgCl) with the cluster [Os 3 (CO) 10 (CH 3 CN) 2 ] yielded two products, [Os 3 (µ-Cl)(CO) 10 (µ-Ag(IMes)] (2) and [(IMes-H)][Os 3 (µ-Cl)(CO) 10 ](µ 4 -Ag)[Os 3 (µ-Cl)(CO) 10 ] (3). Compound (2) is a hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 95 publications
2
44
0
Order By: Relevance
“…31 In all these [M 3 (NHC)(CO) 11 ] (M = Ru, Os) cluster compounds, the very strong basicity of NHCs increases the electron density of the metal atoms to which they are attached and this enhances the tendency of these metals to get involved in oxidative addition processes. 32 It is now well established that NHC-silver(I) complexes, which can be easily made by treating the corresponding imidazolium halide with silver(I) oxide, 33 are able to transfer their NHC ligands to another transition metals, 33 12 ] with [AgCl(Mes 2 Im)] in the presence of Me 3 NO (as decarbonylating reagent), 36 but it was assigned an incorrect structure. A combination of these two factors (unsaturated and electron-rich metals) with the fact that some ligand bonds and cluster metal atoms can be very close to each other rationalize the synthesis of compounds 17-26, in which decarbonylation (and, occasionally, cluster condensation as in 23 and 24) is accompanied by processes that involve the (multiple) activation of ligand bonds.…”
Section: Ruthenium Andmentioning
confidence: 99%
“…31 In all these [M 3 (NHC)(CO) 11 ] (M = Ru, Os) cluster compounds, the very strong basicity of NHCs increases the electron density of the metal atoms to which they are attached and this enhances the tendency of these metals to get involved in oxidative addition processes. 32 It is now well established that NHC-silver(I) complexes, which can be easily made by treating the corresponding imidazolium halide with silver(I) oxide, 33 are able to transfer their NHC ligands to another transition metals, 33 12 ] with [AgCl(Mes 2 Im)] in the presence of Me 3 NO (as decarbonylating reagent), 36 but it was assigned an incorrect structure. A combination of these two factors (unsaturated and electron-rich metals) with the fact that some ligand bonds and cluster metal atoms can be very close to each other rationalize the synthesis of compounds 17-26, in which decarbonylation (and, occasionally, cluster condensation as in 23 and 24) is accompanied by processes that involve the (multiple) activation of ligand bonds.…”
Section: Ruthenium Andmentioning
confidence: 99%
“…The resulting suspension was then heated at 70°C for 16 h. The red solution was cannula filtered and the filtrate reduced to dryness to leave a mixture of red and white solids. The red product was extracted in MeOH (2 mL), filtered, reduced to dryness and the red solid of [Pd 3 (l-CO) 3 ,5.51;N,6.38. Found: C,57.63;H,5.61;N,6.45%.…”
Section: Preparation Of [Pd 3 (L-co) 3 (Imes) 3 ] (1)mentioning
confidence: 99%
“…The red product was extracted in MeOH (2 mL), filtered, reduced to dryness and the red solid of [Pd 3 (l-CO) 3 ,5.51;N,6.38. Found: C,57.63;H,5.61;N,6.45%. Repeated attempts to determine the CHN content gave a consistently low % carbon.…”
Section: Preparation Of [Pd 3 (L-co) 3 (Imes) 3 ] (1)mentioning
confidence: 99%
See 1 more Smart Citation
“…The hitherto reported reactions of NHCs with transition-metal carbonyl clusters and the transformations underwent by the NHC-containing species initially formed in those reactions have shown that the polynuclear character of these metallic compounds or, more precisely, the close proximity of one or more metal atoms to that which is or can be attached to the NHC ligand, is responsible for reactivity patterns (multiple CeH, CeC and CeN bond activation processes [3e6]) that have no parallel in the NHC chemistry of mononuclear complexes. Most of this chemistry has been performed using triruthenium complexes as metal precursors, the hitherto reported works dealing with reactions of NHCs with tetraruthenium complexes being very scarce and they involve only monodentate NHCs [7,8].…”
Section: Introductionmentioning
confidence: 99%